Effect of bone morphogenetic proteins (BMP) on immediately placed and loaded one - piece dental implants in fresh extraction sockets - John Nagy Zaki; Amr Zahran; Riham Omar Ibrahim (Cairo : John Nagy Zaki, 2013)
Objective : The purpose of the present study was to evaluate the effect of the bone morphogenetic proteins on immediately placed and loaded one piece dental implants in fresh extraction sockets . Results : Twenty one - piece implant were successfully osseo- integrated as revealed by the clinical and radiographic assessment . Implant survival rate of 100% was achieved . No significant statistical difference between the 2 gruops regarding the clinical parameters radiographic assessment and the statistical analysis was found
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Periodontology
Issued also as CD
Keywords: Bone morphogenetic proteins; Immediate loading; Immediate placement